Analysis of the sensitivity of in vitro bioassays for androgenic, progestagenic, glucocorticoid, thyroid and estrogenic activity: Suitability for drinking and environmental waters. (February 2017) - Leusch, Frederic D.L.; Neale, Peta A.; Hebert, Armelle; Scheurer, Marco; Schriks, Merijn C.M.
Abstract: The presence of endocrine disrupting chemicals in the aquatic environment poses a risk for ecosystem health. Consequently there is a need for sensitive tools, such as in vitro bioassays, to monitor endocrine activity in environmental waters. The aim of the current study was to assess whether current in vitro bioassays are suitable to detect endocrine activity in a range of water types. The reviewed assays included androgenic ( n = 11), progestagenic ( n = 6), glucocorticoid ( n = 5), thyroid ( n = 5) and estrogenic ( n = 8) activity in both agonist and antagonist mode. Existing in vitro bioassay data were re-evaluated to determine assay sensitivity, with the calculated method detection limit compared with measured hormonal activity in treated wastewater, surface water and drinking water to quantify whether the studied assays were sufficiently sensitive for environmental samples. With typical sample enrichment, current in vitro bioassays are sufficiently sensitive to detect androgenic activity in treated wastewater and surface water, with anti-androgenic activity able to be detected in most environmental waters. Similarly, with sufficient enrichment, the studied mammalian assays are able to detect estrogenic activity even in drinking water samples. Fewer studies have focused on progestagenic and glucocorticoid activity, but some of the reviewed bioassays are suitable for detecting activity in treated wastewater and surface water. Even less is known about (anti)thyroid activity, but the available data suggests that the more sensitive reviewed bioassays are still unlikely to detect this type of activity in environmental waters. The findings of this review can help provide guidance on in vitro bioassay selection and required sample enrichment for optimised detection of endocrine activity in environmental waters. Highlights: Reviewed suitability of in vitro assays to detect endocrine activity in water Included androgenic, progestagenic, glucocorticoid, thyroid and estrogenic activity Some assays are sensitive enough to detect activity in most environmental waters. Others appear not sensitive enough to detect activity even in polluted samples. Findings provide guidance on bioassay selection and required sample enrichment.